Có: M = a3 + b3 + 3ab(a2 + b2) + 6a2b2(a + b)
=> M = (a + b)(a2 - ab + b2) + 3ab((a + b)2 - 2ab) + 6a2b2(a + b)
=> M = (a + b)[(a + b)2 - 3ab] + 3ab[(a + b)2 - 2ab] + 6a2b2(a + b)
=> M = 1 - 3ab + 3ab(1 - 2ab) + 6a2b2 (vì a+b=1)
=> M = 1 - 3ab + 3ab - 6a2b2 + 6a2b2
=> M = 1
Vậy M = 1
M = \(a^3\)+ \(b^3\)+ 3ab ( \(a^2\)+ \(b^2\)) + \(6a^2\)\(b^2\)(a+b)
M = ( a + b ) ( \(a^2\)- ab + \(b^2\)) + 3ab [ \(a^2\)+ \(b^2\)+ 2ab( a + b )
M = \(a^2\)- ab + \(b^2\)+ 3ab ( \(a^2\)+ 2ab + \(b^2\))
Với a + b = 1
M= \(a^2\)- ab + \(b^2\)+ 3ab\(\left(a+b\right)^2\)
M = \(a^2\)- ab + \(b^2\)+ 3ab
M = \(a^2\)+ \(b^2\)+ 2ab
M = \(a^2\)+ 2ab + \(b^2\)
M = \(\left(a+b\right)^2\)
M = 1
Vậy M = 1